Accelerating permafrost collapse on the eastern Tibetan Plateau. (23rd April 2021) - Gao, Tanguang; Zhang, Yulan; Kang, Shichang; Abbott, Benjamin W; Wang, Xiaoming; Zhang, Tingjun; Yi, Shuhua; Gustafsson, Örjan
Abstract: Permafrost collapse can rapidly change regional soil-thermal and hydrological conditions, potentially stimulating production of climate-warming gases. Here, we report on rate and extent of permafrost collapse on the extensive Tibetan Plateau, also known as the Asian Water Tower and the Third Pole. Combined data from in situ measurements, unmanned aerial vehicles (UAV), manned aerial photographs, and satellite images suggest that permafrost collapse was accelerating across the Eastern Tibetan Plateau. From 1969 to 2017, the area of collapsed permafrost has increased by approximately a factor of 40, with 70% of the collapsed area forming since 2004. These widespread perturbations to the Tibetan Plateau permafrost could trigger changes in local ecosystem state and amplify large-scale permafrost climate feedbacks.